Associação entre depressão e glaucoma em pacientes atendidos em um hospital de referência em oftalmologia - VIEIRA, Juliana Almeida (2019)
Introduction: Glaucoma is a chronic disease with global significance as it negatively impacts visual function and may cause irreversible blindness, leading to activity limitation, isolation and depression, a commonly overlooked comorbidity in the ophthalmological practice. Purpose: to assess the prevalence of depression in glaucoma patients in an ophthalmic service. Methods: The present descriptive, observational cross-sectional study included 51 glaucoma patients seen on the eye clinic of the Hospital Universitário Bettina Ferro de Souza (HUBFS). The Patient Health Questionnaire-9 (PHQ-9) and a socio-economic and epidemiological questionnaire were administered to all patients for depression screening and evaluation of its risk factors. Objective measures of visual function, including bestcorrected visual acuity and Mean Deviation (MD) of visual field, were collected from the patients’ medical records. Results: The prevalence of depression found was 35,3% (n=18). Female sex (p<0,003), residence outside the metropolitan area (p<0,001) and self-report of worsening visual acuity as consequence of glaucoma (p<0,004) were considered predictors of depression in glaucoma patients. Conclusions: Glaucoma patients were found to have high prevalence of depression, showcasing the need of special care when dealing with them. However, measures of visual field and acuity were not considered risk factors for depression.